Dried blood spot and mini-tube blood sample collection kits for postal HIV testing services: a comparative review of successes in a real-world setting. (2nd August 2018) - Page, Matthew; Atabani, Sowsan F; Wood, Martyn; Smit, Erasmus; Wilson, Steven; Atherton, Carol; Davenport, Clare F; Hartland, Daniel; Simpson, Mark; Taylor, Stephen
Abstract : Objectives: This is a comparative review between using dried blood spot (DBS) and mini-tube (MT) HIV sampling kits as part of an online sexually transmitted infection (STI) postal testing service. England has recently seen increases in internet-based and postal (eHealth) STI services. Expanding accessibility and testing for patients, cost implications and narrowing the HIV undiagnosed margin are drivers for this. Methods: In 2017, data were reviewed from an online postal STI kit requesting service at a time of transitioning from MT to DBS. We compared the STI postal kit and HIV blood sample return rates, and the successful processing/analysis rates of the DBS and MT kits. Descriptive statistics were applied to participant characteristics, with Pearson's χ 2 or Fisher exact test used to demonstrate statistical differences. We also describe and calculate a 'request-to-result ratio' (RRR) for both kit types. The RRR is defined as the number of online kit requests required to produce one successfully analysed result. Results: 550 STI postal kit requests from a North-West of England region were reviewed from 13 June 2017 to 22 September 2017 (275 MT, 275 DBS). Baseline characteristics between the two groups were comparable (63% woman, 90% white British and 86% heterosexual with a median age of 26 years). The successful processing rate for the DBS was 98.8% c.f. 55.7% for the MT (p<0.001). The RRR for MT was 2.96, c.f. 1.70 for DBS. There was a 5.4% false positive HIV rate in the MT c.f. none in the DBS. Conclusions: This comparative analysis suggests that in this community setting, the use of postal HIV DBS kits resulted in a significantly improved RRR compared with MT. The biggest factor was the large number of MT samples not analysed due to inadequate blood volumes. The unexpected level of false positive results in the MT samples needs confirming in larger studies.